Cyber Security in Indonesian Higher Education Institutions: Lessons Learned from Recent Cyber Attacks - Marpaung, Jonathan Nahum (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Cyber security is paramount to the sustainability of higher education institutions as more institutions move their information system to the cloud and allow stakeholders to access their information technology services from on-campus WIFI and mobile devices. This study aims to understand Indonesian higher education's current cyber security landscape by analyzing recent cyber-attacks that hit all sectors, notably higher education. Recent news articles and government reports related to cyber-security were analyzed using document analysis. This study found that data theft attacks were the number one cyber threat that higher education institutions faced, followed by attacks on institutional websites, social media pages, and personal mobile devices. This study found that the nature of recent cyber-attacks was consistent with the assessment posed by previous literature that stakeholders’ recent level of ability in cyber-security is not where it is supposed to be. The potential impact of future cyber-attacks on institutions and stakeholders is significant, underscoring the importance of this new understanding, which can help institutions prepare their stakeholders better to mitigate such threats.